Nursing knowledge as a response to societal needs - Skela-Savič, Brigita (Zdravstveno varstvo, 2011)
Introduction: As the population needs for health care at the local level become integrated into the global context, nurses are given the opportunity to make a significant contribution to the modernization of the healthcare system and gain importance and recognition from the political perspective. Nursing today is confronted with the needs and demands of both healthy and ill populations - these can be the result of changing demographics, new technologies, a growing awareness of the rights and voiced expectations of service users etc. Slovenian nurses have the opportunity to make a significant contribution to the modernization of the Slovenian healthcare system. This can be achieved by learning from the experiences of other countries and by exploring and addressing existing aspects of the need to gain professional status. Methods: A review of the international literature indexed in the CINAHL database was performed for the period January - August 2010. The key phrases used were: "nursing skills and knowledge", "nursing future and politics", "nursing future and responsibility", "nursing future andleadership". We used only abstracts in English. A total of 343 abstracts were retrieved and assessed. All abstracts that did not include issues relatedto the importance of nursing knowledge and the importance of connecting nursing knowledge with patient needs were excluded. Twenty-two articles in total were included. A qualitative synthesis of the conclusions from each of the articles included was conducted, from which content codes were generated. The codes were then placed into content categories. Results: Forty-seven qualitative codes were identified and semantically divided into 7 categories: public perception of nurses and the importance of knowledge; awareness at the personal and professional levels; adapting health care skills and knowledge, and the number of health care professionals, to future needs; importance of new nursing skills and knowledge, and of skill transfer; research as the source of new knowledge and development; assuming responsibility for conducting evidence-based nursing; emphasizing cooperation and communication. Discussion: Based on the established qualitative categories in our research, we developed an explanatory model that is a good starting point for reflecting on where nursing is today and where it should beheading in the future, and is recommended for nurses, nursing managers, deans of nursing colleges, officials in nursing associations and others. Research findings are especially relevant for countries in which nursing is currently a poorly developed scientific discipline and in which steps need to be taken fast to promote knowledge development and the role of nurses in society.
Keywords: Profesionalni razvoj; Svetovni trendi; Zdravstvena nega